Uncertainty of continuous ∆CO-based ∆ffCO2 estimates derived from 14C flask and bottom-up ∆CO/∆ffCO2 ratios - Maier, Fabian; Levin, Ingeborg; Conil, Sébastien; Gachkivskyi, Maksym; Denier van der Gon, Hugo A. C.; Hammer, Samuel (EGUsphere, 2023)
Abstract. Measuring the 14C / C depletion in atmospheric CO2 compared to a clean-air reference is the most direct way to estimate the recently added CO2 contribution from fossil fuel (ff) combustion (∆ffCO2) in ambient air. However, since 14CO2 measurements cannot be conducted continuously nor remotely, there are only very sparse 14C-based ∆ffCO2 estimates available. Continuously measured tracers like carbon monoxide (CO), which are co-emitted with ffCO2 can be used as additional alternative proxies for ∆ffCO2, provided that the ∆CO / ∆ffCO2 ratios can be determined correctly. Here, we use almost 350 14CO2 measurements from flask samples collected between 2019 and 2020 at the urban site Heidelberg in Germany, and corresponding analyses from more than 50 afternoon flasks collected between September 2020 and March 2021 at the rural ICOS site Observatoire pérenne de l'environnement (OPE) in France, to calculate average ∆CO / ∆ffCO2 ratios for those sites. By dividing the hourly ∆CO excess observations by the averaged flask ratio, we construct continuous and bias-free ∆CO-based ∆ffCO2 records. The comparison between ∆CO-based ∆ffCO2 and 14C-based ∆ffCO2 from the flasks yields a root-mean-square deviation (RMSD) of about 4 ppm for the urban site Heidelberg and of 1.5 ppm for the rural site OPE. While for OPE this uncertainty can be explained by observational uncertainties alone, for Heidelberg about half of the uncertainty is caused by the neglected variability of the ∆CO/∆ffCO2 ratios. We further show that modelled ratios based on a bottom-up European emission inventory would lead to substantial biases in the ΔCO-based ∆ffCO2 estimates for Heidelberg, and also for OPE. This highlights the need for an ongoing observational calibration/validation of inventory-based ratios, if those shall be applied for large-scale ΔCO-based ∆ffCO2 estimates, e.g. from satellites.
Im Titel ist die Zahl 2 jeweils tiefgestellt, 14 ist hochgestellt
Gesehen am 05.02.2024